Long-term physical performance trends across the five confederations: Evidence from the 19th to 22nd FIFA World Cup editions (2010–2022) - Xiao Yang; Liangzhu Feng (PLoS ONE, 2026)
Background Physical performance demands in elite international football have evolved substantially in recent decades, yet longitudinal comparisons across FIFA confederations remain limited. Objective This study examined long-term changes in physical performance demands among outfield players from five confederations (UEFA, CONMEBOL, CONCACAF, CAF, and AFC) using tracking data from 225 matches at the 2010–2022 FIFA World Cups. Methods Generalised mixed linear models were used to estimate changes in total distance, top speed, sprint (>25 km·h ⁻ ¹), low-intensity running distance (<15 km·h ⁻ ¹), and high-intensity running distance (≥15 km·h ⁻ ¹), with confederation as the main factor and match status, location, and team and opponent strength controlled. Results Across confederations, substantial increases were observed in top speed, sprint, and low-intensity running distance from 2010 to 2022, indicating a uniform rise in speed-related demands. In contrast, changes in total distance and high-intensity running distance were confederation-specific. Total distance increased between 2018 and 2022 in AFC, CONCACAF, and UEFA, but showed no substantial change in CONMEBOL. High-intensity running distance declined in AFC, CONMEBOL, and UEFA, while changes in CAF were trivial. Conclusion These findings indicate that speed-related demands have increased globally, whereas total and high-intensity running demands remain region-specific across FIFA World Cup editions.